Sustainability without Subsidy: Public Case for Vertically Integrated Rail Oligopolies for Freight. Issue 12 (December 2019) - Allen, John G.; Newmark, Gregory L.
Maintaining rail freight networks without subsidy is an important transportation policy concern. Today's vertically integrated rail oligopolies (VIROs) in the United States, Canada, and Mexico have enabled rail freight to be commercially self-sustaining. A combination of favorable geography involving a choice of railroads for most longer hauls and commercial freedom for railroads to set prices without prior regulatory approval have helped create a situation in which North American freight railroads are self-sustaining without government subsidies. This research examines the development of VIROs in the United States, Canada, and Mexico today. A largely hands-off policy, combined with a willingness to allow railroads to accumulate enough money to maintain their physical plants to high standards, have led to today's major freight railroad duopolies in the eastern and western United States, Canada, and Mexico. Despite some complaints from shipper interests, today's VIROs are largely stable (with the possible exception of broader policy changes in Mexico). Lawmakers and regulators should ensure that any future mergers do not adversely affect the performance of what has thus far been a largely satisfactory model.